Coastal Zones Ecosystem Services: From Science to Values and Decision Making - Turner, R. Kerry (Springer, 2015)
This book applies the ‘ecosystem services’ framework to coastal environments, showing how it could facilitate an adaptive management strategy. The contributors describe a decision support system (DSS) based on the 3 Ps – pluralism, pragmatism and precaution – that leads to a more flexible, ‘learn by doing’ approach to the stewardship of coastal environments. The book lays out a “Balance Sheets Approach” to formatting, interrogating and presenting data and findings. The opening chapter defines coastal zones, their characteristics and natural resources, and describes their complex and dynamic nature. The chapter shows that large-scale trends and pressures have led to a global loss of 50% of marshes, leading to significant declines in biodiversity and habitat. Part I presents a conceptual framework, describes natural science techniques for coastal and shelf modeling, and describes valuation of ecosystem services. Part II outlines practical ecosystem indicators for coastal and marine ecosystem services, reviews literature on valuation of coastal and marine ecosystem services, explores scenarios, outlines marine and coastal ecosystem services data and offers tools for incorporating data into decision-making. PART III offers case studies including one linking the ecosystem services of Marine Protected Areas to benefits in human wellbeing; and another on valuing blue carbon captured by oceans and coastal ecosystems. Also included are a study of managed realignments and the English coastline and their value estimate transferability; and studies of the impact of jellyfish blooms on recreation in the UK and on fisheries in Italy.